Keunikan huruf vokal dalam bahasa arab - Kamal, Muhammad Zulfa; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
The presence of vowels in a language is one of the essential elements that make up a language. Different languages sometimes have different vowels and consonants. This serves as a distinguishing feature of one language from another. This paper will discuss the uniqueness and distinctiveness of vowels in the Arabic language. The composition of this article uses the library research method with a descriptive qualitative presentation of the results. The results of this study indicate that the Arabic vowel system has distinctive phonological characteristics, particularly in the division of short and long vowels, which not only function to differentiate meaning but also influence morphological and syntactic structures. Furthermore, the presence of mad letters, diphthongs, and variations in vowel articulation provide their own dynamics in the process of learning and pronouncing Arabic. Literature analysis also reveals that these vowel variations play an important role in the clarity of meaning, reading rhythm, and phonetic beauty in both linguistic and religious contexts. Therefore, this study is expected to contribute to the understanding of Arabic phonology and serve as a reference in linguistic studies, Arabic language teaching, and religious phonetics studies.